Customer Journey Definition and Implementation of Segmentation in a Financial Services Institute - Freire, Carolina Nastassia de Moura (2023)
Project Work presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Marketing Intelligence